2006
DOI: 10.1098/rstb.2006.1878
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen tunnelling in enzyme-catalysed H-transfer reactions: flavoprotein and quinoprotein systems

Abstract: It is now widely accepted that enzyme-catalysed C-H bond breakage occurs by quantum mechanical tunnelling. This paradigm shift in the conceptual framework for these reactions away from semiclassical transition state theory (TST, i.e. including zero-point energy, but with no tunnelling correction) has been driven over the recent years by experimental studies of the temperature dependence of kinetic isotope effects (KIEs) for these reactions in a range of enzymes, including the tryptophan tryptophylquinone-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
77
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 98 publications
1
77
0
Order By: Relevance
“…The advantage of this experimental method is that the temperature dependence of KIEs is highly sensitive to the changes in the hydrogen donor and acceptor distance (DAD), which can modulate the degree of the nuclear wave function overlap between the donor and acceptor states of the hydride being transferred (27,30). As suggested by several phenomenological models, referred to here as Marcus-like models, temperature-independent KIEs indicate a short and narrow distribution of DADs, whereas temperature-dependent KIEs are associated with longer and broader DAD distributions with lower fluctuation frequency (27,(31)(32)(33)(34). QM/MM calculations have confirmed that the DAD is the dominant factor in determining the temperature dependence of the KIE in ecDHFR (6,7,10,28).…”
mentioning
confidence: 99%
“…The advantage of this experimental method is that the temperature dependence of KIEs is highly sensitive to the changes in the hydrogen donor and acceptor distance (DAD), which can modulate the degree of the nuclear wave function overlap between the donor and acceptor states of the hydride being transferred (27,30). As suggested by several phenomenological models, referred to here as Marcus-like models, temperature-independent KIEs indicate a short and narrow distribution of DADs, whereas temperature-dependent KIEs are associated with longer and broader DAD distributions with lower fluctuation frequency (27,(31)(32)(33)(34). QM/MM calculations have confirmed that the DAD is the dominant factor in determining the temperature dependence of the KIE in ecDHFR (6,7,10,28).…”
mentioning
confidence: 99%
“…In fact it has been long thought that electrons can move along enzymes in a manner similar to that observed in semiconductors [35], which may be due to quantum tunnelling [36]. It also appears that enzymes also utilise proton tunnelling [37]. Life may use thermal vibrations to pump coherence, which results in a phenomenon known as quantum beating.…”
Section: The Emergence Of Quantum Biologymentioning
confidence: 99%
“…4) and slower time scales 5,31,32 and are often attributed to conformational (classical) distributions of the D-A distance 4,5,7,[33][34][35] . Other approaches 12,27,36 factor out and quantize the D-A vibration (~100 fs), as well as the much higher frequency (~10 fs) vibrational mode of the tunneling particle, which is a common feature in all analytical models (see Supplementary Discussion 4).…”
Section: Deep Tunneling Modelsmentioning
confidence: 99%